Nicaraguan population data on LDLR, GYPA, D7S8, HBGG, GC and HLA-DQA1 loci - Morera, Bernal; Sánchez-Rivera, Gerardo; Jiménez-Arce, Gerardo; Calafell, Francesc; Morales-Cordero, Ana Isabel (Revista de Biología Tropical, 2001)
Nicaraguans have become the most numerous and fastest increasing minority in Costa Rica: at present they represent around 6 % of the total population of the country. We have analyzed the allele and genotype frequencies of six PCR-based genetic markers (LDLR, GYPA, HBGG, D7S8, GC, and HLA-DQA1) in 100 unrelated Nicaraguans living in Costa Rica. All loci studied were in Hardy-Weinberg equilibrium. Some statistical parameters of forensic interest were also calculated (h, PD and CE). Allele frequencies of the markers HLADQA1 and GYPAwere found to be significantly different between the populations of Nicaragua and Costa Rica. Nevertheless, genetic distances showed that Nicaragua is close to other Hispanic-admixed populations like those from Argentina, Chile, Colombia, Costa Rica, and USA Hispanics. The loci set was assessed to be useful for paternity testing and individual identification in the Nicaraguan population residing in Costa Rica.